Pembangunan dan penilaian keberkesanan persekitaran pembelajaran sosial menerusi web bagi menggalakkan pembelajaran aktif - Johari, Nur Ain (2010)
Nowadays, current technology has inspired a lot of new approaches in learning process including the e-learning. The use of Learning Management System (LMS) for example can help lecturers to plan their teaching more effectively and facilitate students to access it at their own pace and time. However LMS is still bound to the formal learning environment as the lecturers are the one who decide the activities and patterns of learning inside the e-learning. Therefore, this project aimed to look at the potential of the integration of LMS with an informal learning environment, also known as Social Learning Environment (SLE), particularly in increasing active participitation from students in e-learning. The topic ‘Grafik’ in Technology and Media Design subject at tertiary level is chosen as the learning content in this system. Questionnaire was distributed to ten respondents who were students of Bachelor of Education (Educational Technology). Open interviews were also conducted to two respondents from the same sample. The result of the study shows that students accept this e-learning system as a medium of learning. Besides that, the ease level for students to learn, the effectiveness level of the system to help students learning and the most popular characteristics in the integration of the LMS and SLE approach were also considered. It is hoped that it can be a new medium in e-learning in enhancing active involvement from students in learning process as well as the medium of distribution and sharing of teaching and learning resources among lecturers and students.